Peran Media Multimodal Berbasis Mikrodrama AI sebagai Strategi Menulis Kreatif Naskah Drama: Studi Kasus di SMA - Nurul Aini; Muhamad Haryanto (Edu Berkah Khatulistiwa, 2026)
This study aims to describe the role of AI-based microdrama multimodal media as a strategy for creative playwriting in high school. The study employs a qualitative approach using the case study method. The research subjects were ninth-grade students and Indonesian language teachers at SMA N 2 Batang. Data were collected through interviews, observations, and documentation, and were subsequently analyzed using data condensation, data presentation, and conclusion techniques. The results of the study indicate that AI-based microdrama multimodal media serves as a source of inspiration for developing story ideas, helps students understand dramatic elements through a combination of text, visuals, and audio, and enhances student motivation and participation in the creative writing process. Furthermore, the use of this medium supports the development of imagination, creativity, and the ability to structure plot and dramatic dialogue more effectively. However, its implementation requires teacher guidance to ensure that the use of technology remains aligned with learning objectives. Thus, AI-based microdrama multimodal media holds potential as a strategy to support the learning of creative drama script writing at the high school level.